Inhibitory Effect of Garlic and Vitamin C on Candida Albicans - Lufthansyahrizal, Muhammad Fauzi; Andriana, Kusuma; Nurainiwati, Sri Adila (Folia Medica Indonesiana, 2022)
Highlight: 1. Garlic and Vitamin C effect on Candida Albicans. 2. Vitamin C has the ability to inhibit C. albicans in PBS media but it did not have significant MIC due to the presence of glucose in the media if combined with garlic petroleum extract. Abstract: Garlic can downregulate ECE1, a gene that regulates the production of candidalysin as a virulence factor for C. albicans. Allicin in garlic has antifungal properties because allicin can penetrate cell membranes and damage cell organelles such as vacuoles and mitochondria, causing irreversible structural and functional damage that leads to cell death. Garlic that is processed into extracts also has antifungal abilities. Purely squeezed garlic extract had a MIC of 50%, while the ethanol extract of garlic had a MIC of 40%. This difference is thought to be due to differences in the use of concentrations used and the use of extract solvents. Vitamin C can inhibit C. albicans in PBS media, there is an active metabolism and oxygen, low free iron concentration, there is mitochondrial inhibition ongoing, and in the early stationary growth phase. However, the combination of garlic petroleum ether extract and vitamin C did not show significant MIC due to the presence of glucose in the media, which could increase the growth of C.albicans.